Molecular characteristics and therapeutic vulnerabilities across paediatric solid tumours - Jones, David T. W.; Banito, Ana; Grünewald, Thomas G. P.; Haber, Michelle; Jäger, Natalie; Kool, Marcel; Milde, Till; Molenaar, Jan J.; Nabbi, Arash; Pugh, Trevor; Schleiermacher, Gudrun; Smith, Malcolm A.; et al. (Nature reviews. Cancer, 2019)
Paediatric solid tumours are known to be divergent from adult malignancies. This Review describes the molecular landscape of paediatric solid tumours, the therapeutic vulnerabilities that can be targeted and the preclinical models available to test the efficacy of investigational drugs with a view to accelerating translational progress.